2010
DOI: 10.1093/nar/gkq1149
|View full text |Cite
|
Sign up to set email alerts
|

Protein inactivation in mycobacteria by controlled proteolysis and its application to deplete the beta subunit of RNA polymerase

Abstract: Using a component of the Escherichia coli protein degradation machinery, we have established a system to regulate protein stability in mycobacteria. A protein tag derived from the E. coli SsrA degradation signal did not affect several reporter proteins in wild-type Mycobacterium smegmatis or Mycobacterium tuberculosis. Expression of the adaptor protein SspB, which recognizes this modified tag and helps deliver tagged proteins to the protease ClpXP, strongly decreased the activities and protein levels of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 38 publications
4
110
0
Order By: Relevance
“…SspB is an Escherichia coli-derived protein that can deliver proteins containing the DAS+4-tag to the degradation machinery in mycobacteria (16,17). In an Msm strain in which transcription of sspB and the luciferase encoding luxAB-DAS operon were controlled by TSC10 and T38, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SspB is an Escherichia coli-derived protein that can deliver proteins containing the DAS+4-tag to the degradation machinery in mycobacteria (16,17). In an Msm strain in which transcription of sspB and the luciferase encoding luxAB-DAS operon were controlled by TSC10 and T38, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For Mtb, 7H11 was supplemented with 10% (vol/vol) Middlebrook oleic acid-albumin-dextrose-catalase (Becton Dickinson); 7H9 was supplemented with 0.2% glycerol, 0.05% tyloxapol, 0.5% BSA, 0.2% dextrose, and 0.085% NaCl. Preparation of cell lysates; immunoblot analyses; and measurements of fluorescence, luminescence, and β-galactosidase activity were performed as described previously (7,13,16,43). To measure the kinetics of luciferase inactivation during starvation, Msm was transferred into PBS with 0.05% tyloxapol (PBST).…”
Section: Methodsmentioning
confidence: 99%
“…A solution to this problem is to specifically target the encoded gene product for conditional depletion (29). In doing so, the gene remains in its natural context, and the encoded product functions normally at the appropriate dose prior to its removal.Prior studies have demonstrated the utility of this approach for specific cases by reengineering target proteins such that they contain a peptide degradation signal that is recognized by a processive protease (7,15,20,24,29,53). In early examples, a degradation peptide that has a weakened affinity for the protease was selected, and then an adapter protein that increases the effective local concentration of the target near the protease to increase degradation was conditionally expressed (20,29).…”
mentioning
confidence: 99%
“…To further reduce the amount of CC3721, we added at the end of the gene a region of the transfer-messenger RNA (tmRNA) present in C. crescentus that codes for a peptide that marks the protein for degradation (48). A similar approach was used previously with cytoplasmic proteins (49,50); however, this is to our knowledge the first time that this approach has been used with a periplasmic protein. In the absence of xylose, the resultant strain (SP3) reached stationary phase (optical density at 600 nm [OD 660 ] of 1.2) in the first overnight (ON) culture.…”
Section: Resultsmentioning
confidence: 99%